Outside Blockholders' Monitoring of Management and Debt Financing: An Alternative Perspective - Nikolaev, Valeri V. (Contemporary Accounting Research, 2015)
Abstract Liao ( ) argues that the monitoring by large outside shareholders (blockholders) exacerbates the conflict between debt and equity and in turn affects the choice and structure of debt financing. The study contends that private debt is more immune to the increase in debt‐equity conflict. Consistent with this argument, companies with outside blockholders are inclined to issue private debt over public debt. Further, private debt exhibits less price protection but relies on more protective covenants than does public debt. The findings are interesting and intuitive. I evaluate the economic arguments in the paper and discuss some of the challenges that the study faces. My conclusion is that the interpretation of the results is more complex than the one the study presents. I offer a broader framework that can be used to shed light on why the governance structure combines equity blockholders and private debt issuance. I also discuss several questions to be addressed by future research.